Use of 1-methylcyclopropene to complement refrigeration and ameliorate chilling injury symptoms in summer squash - Massolo, Juan Facundo (2013)
To elucidate the role of ethylene in summer squash [Cucurbita maxima var. Zapallito (Carr.) Millan] postharvest responses, harvested fruit was treated with the inhibitor of ethylene action 1-methylcyclopropene (1-MCP, 1 μL L⁻¹) and stored at 10 or 0 °C for 14 or 19 days, respectively. Deterioration, chilling injury (CI), weight loss, surface color, firmness, respiration rate, acidity, sugars, and antioxidants were determined. At 10 °C 1-MCP treated fruit showed lower deterioration and weight loss. The inhibition of ethylene action delayed yellowing, softening, and respiration, and prevented the increase of acidity. Chilling injury, manifested as shrunken areas and surface depressions, yellowing and softening were reduced in 1-MCP-treated fruit stored at 0 °C. Sugars and antioxidants were not affected. Results suggest that ethylene is involved in senescence and CI development in summer squash. Inhibition of its action by 1-MCP could be useful to prevent deterioration and maintain quality.